Interpretation of the Constitution on the Arrangement of State-Owned Enterprises in the National Economic System Based on the Decision of the Constitutional Court - Harvelian, Agnes; Safa’at, Muchamad Ali; Widiarto, Aan Eko; Qurbani, Indah Dwi (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The constitutional interpretation of the regulation of State-Owned Enterprises (BUMN) is still looking for the right method, BUMN as the embodiment of the constitution for the state's responsibility in managing strategic resources that are used as wide as possible for the prosperity of the people. Submission of a judicial review to the Constitutional Court regarding BUMN can show the direction of constitutional interpretation given by the judges of the Constitutional Court. This article examines whether the constitutional interpretation of SOE arrangements is in accordance with Indonesia's national economic system. The method of approach in this writing is descriptive analysis which explains and analyzes the constitutional interpretation of SOE regulations. the results of the study reveal that the constitutional court has carried out its duties in accordance with the basic principles and principles of the constitution. The Constitutional Court in every decision in the field of BUMN dominates its interpretation by using an originalist interpretation.